Wartości globalizacyjne w rzeczywistości kulturowej Europy Wschodniej - Chodubski, Andrzej (Eastern Review, 2012)
Article dedicated to the problem of globalization influence on East European cultural space. Author points that globalization is powerful force significantly altering local cultural identity given states, nation and ethnic groups, moreover it’s responsible for dualistic picture of world of socio-political values. It’s important – according to author – to take into account that globalization helps to unveil openness to the signs of the new civilization, on the other hand globalization ensues cultural life’s diversification and what is more important affirmation of regional and local identity in national and ethnical dimension. In East European area we witness strong roots of traditional political culture genre that can be characterize by the presence of acceptance for establishments, ceremonies and hierarchical dependency. Such ideas as democracy, self-government, law have their own distinctive features, deeply rooted in local tradition. Cultural and civilizational model of life in eastern part of Europe is embedded in notion of frontier that combines such ideas as friend and foe. Globalization singes influence are reinforced by mass media impact and at the same time they gather significant social acceptance.